2018
DOI: 10.1007/s00247-018-4144-6
|View full text |Cite|
|
Sign up to set email alerts
|

Carotid artery intima-media thickness measurement in children with normal and increased body mass index: a comparison of three techniques

Abstract: BackgroundCommon carotid artery intima-media thickness is a marker of subclinical atherosclerosis. In children, increased intima-media thickness is associated with obesity and the risk of cardiovascular events in adulthood.ObjectiveTo compare intima-media thickness measurements using B-mode ultrasound, radiofrequency (RF) echo tracking, and RF speckle probability distribution in children with normal and increased body mass index (BMI).Materials and methodsWe prospectively measured intima-media thickness in 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…B-Mode imaging or radiofrequency multiple M-line analysis, influence the magnitude of IMT and, therefore, limit the comparability of the included studies. Thus, only one technique should be performed in prospective studies (67). Following Skilton et al (68), the choice of location of IMT measurement-at the carotid artery or the aorta-should be decided depending on the target group and the individual goal of each study.…”
Section: Resultsmentioning
confidence: 99%
“…B-Mode imaging or radiofrequency multiple M-line analysis, influence the magnitude of IMT and, therefore, limit the comparability of the included studies. Thus, only one technique should be performed in prospective studies (67). Following Skilton et al (68), the choice of location of IMT measurement-at the carotid artery or the aorta-should be decided depending on the target group and the individual goal of each study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in patients aged 1 month to 2 years, the median internal diameters of the IJV and ICA are reportedly 8.9 mm and 4.3 mm, respectively [15] . In addition, the reported mean intima-media thickness of the ICA in children measured by B-mode US is 0.56 mm [16] .…”
Section: Methodsmentioning
confidence: 99%
“…Various techniques were used to detect the edge like thresholding technique [2], marker controlled watershed [9], gradient based [10], active contour [11], first order absolute moment edge operator [12]. Jalbout et al [13] has found that main reason behind atherosclerosis disease in childhood is obesity. The author has given the comparison of three RF techniques to measure the IMT of carotid artery.…”
Section: Literature Surveymentioning
confidence: 99%